Circadian changes in cortical excitability in restless legs syndrome - UYSAL, ÖMER; Gunduz, Aysegul; ADATEPE, Nurten Uzun; KIZILTAN, Meral E.; KARADENIZ, Derya; Uysal, Omer (My University, 2012)
Various investigations have revealed a widespread and somewhat controversial pattern of cerebral, cerebellar and brainstem involvement in the pathophysiology of restless legs syndrome (RLS). However, several studies which investigated functional or structural aspects indicated cortical involvement in RLS. In this study, we aimed to analyze circadian changes of cortical excitability in idiopathic RLS patients by means of transcranial magnetic stimulation (TMS). Eleven idiopathic RLS patients and eight healthy age and sex matched subjects were investigated using single-pulse TMS and motor nerve conduction studies during early afternoon when there were no symptoms and late at night (22:00-23:00) when the symptoms reappeared. Central motor conduction time, latencies and amplitudes of scalp and cervical motor evoked potentials, resting and active motor thresholds, and cortical silent period were measured. Measured parameters were similar between RLS patients and healthy subjects during the daytime. At night, cortical silent periods tended to shorten, and motor thresholds tended to decrease in the RLS group, whereas in controls they tended to increase.